Integrasi Teori Trilogi Juran dan Teori PDCA Edward Deming dalam Meningkatkan Mutu Pendidikan di Sekolah - Mahmuda, Komariyatul; Faslah, Romi (AL-WIJDÃN Journal of Islamic Education Studies, 2025)
The quality of education is one of the main focuses of every educational institution. To improve the quality of education that is clear and measurable, one of the steps that can be taken is to integrate Juran's Trilogy theory and Edward Deming's PDCA Theory in education quality management. Data collection in this study used the literature method with content analysis techniques. The focus of the study in this research includes how the principle of improving the quality of education, analysis of Edward Deming's PDCA theory, Juran's Trilogy Theory, and their integration in improving the quality of education. The results show that the principles of quality management improvement include: Customer focus, strong leadership management, continuous improvement, involvement of all employees, systematic and planned processes, and data-based decision-making information. In improving the quality of education, Deming used the PDCA cycle (Plan-Do-Check-Action), while Juran used a three-step approach (Juran Trilogy): Quality planning, quality control, and quality improvement. The integration of both can build a strong quality culture based on holistic philosophy and values, systematic structures and processes that proactively prevent defects to achieve measurable and sustainable quality, and balance human aspects, implementation systems, and optimal results.   Kata Kunci: Juran's Trilogy Theory, Edward Deming's PDCA Theory, Education Quality